Effectiveness of Thermal Properties in Thermal Energy Storage Modeling - Torres Sevilla, Law; Radulovic, Jovana (Frontiers in Mechanical Engineering, 2021)
This paper studies the influence of material thermal properties on the charging dynamics in a low temperature Thermal Energy Storage, which combines sensible and latent heat. The analysis is based on a small scale packed bed with encapsulated PCMs, numerically solved using COMSOL Multiphysics. The PCMs studied are materials constructed based on typical thermal properties (melting temperature, density, specific heat capacity (solid and liquid), thermal conductivity (solid and liquid) and the latent heat) of storage mediums in literature. The range of values are: 25–65°C for the melting temperature, 10–500 kJ/kg for the latent heat, 600–1,000 kg/m3 for the density, 0.1–0.4 W/mK (solid and liquid) for the thermal conductivity and 1,000–2,200 J/kgK (solid and liquid) for the specific heat capacity. The temperature change is monitored at three different positions along the tank. The system consists of a 2D tank with L/D ratio of 1 at a starting temperature of 20°C. Water, as the heat transfer fluid, enters the tank at 90°C. Results indicate that latent heat is a leading parameter in the performance of the system, and that the thermal properties of the PCM in liquid phase influence the overall heat absorption more than its solid counterpart.